THE EFFECT OF THE INDEPENDENT LEARNING POLICY ON STUDENT ACHIEVEMENT THROUGH TEACHER PERFORMANCE AS A MEDIATING VARIABLE - Sumardiyanto, Sumardiyanto; Dassucik, Dassucik; Endang Sri D., Lusi (Consilium: Education and Counseling Journal, 2025)
This study examines the impact of the Independent Learning Policy on student achievement, focusing on the mediating role of teacher performance. Utilizing a quantitative research approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis through SmartPLS 4, the study analyzed data collected from a sample of 196 grade 9 students from three junior high schools in Situbondo Regency. The results indicate that the Independent Learning Policy significantly influences both teacher performance (path coefficient = 0.668, T-statistic = 19.174, p < 0.000) and student achievement (path coefficient = 0.414, T-statistic = 7.741, p < 0.000). Teacher performance was also found to have a substantial direct impact on student achievement (path coefficient = 0.558, T-statistic = 9.900, p < 0.000) and acted as a critical mediator, amplifying the policy's effect on student outcomes (indirect path coefficient = 0.373, T-statistic = 8.273, p < 0.000). The adjusted RÂ² values further reinforce the model's robustness, with 44.3% of teacher performance variance and 78.9% of student achievement variance explained by the Independent Learning Policy and teacher performance. These findings emphasize the necessity of empowering teachers through professional development and resource allocation to maximize the effectiveness of educational policies. This study contributes to the theoretical understanding of policy implementation in education and offers practical recommendations for enhancing educational outcomes in junior high schools.